Women, food, and diet in the middle ages - Vaughan, Theresa A., 1966- author. Link
1 online resource.
Keywords: What can anthropological and folkloristic approaches to food, gender, and medicine tell us about these topics in the Middle Ages beyond the textual evidence itself? Women, Food, and Diet in the Middle Ages: Balancing the Humours uses these approaches to look at the textual traditions of dietary recommendations for women's health, placed within the context of the larger cultural concerns of gender roles and Church teachings about women. Women are expected to be nurturers, healers, and the primary locus of food provisioning for families, especially women of the lower social classes, typically overlooked in the written record. This work illuminates what we can know about women, food, medicine, and diet in the Middle Ages, and examines how the written medical tradition interacts with folk medicine and other cultural factors in both understanding women's bodies and their roles as healers and food providers.